In Wikipedia We Trust: A Case Study — Extended Abstract - Merchant, Arpit; Shah, Darshit; Singh, Navjyoti (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
Wikipedia follows an open editing model that allows anyone to edit any entry. This has led to questions about the credibility and quality of information on it. Yet, it remains one of the most widely visited online encyclopedias. In this paper, we present a discussion of the various factors that influence the trust that users have on Wikipedia through a framework consisting of personal, social and functional elements. We further argue that digital signals and non-verbal cues also play an important role in determining trust on the various agents of the system.